1940 Rodeo Team (1940)
Winners of Intercollegiate Rodeo at Victorville, April 13, 1940. Left to right--Carl Miller, Gilmore Ross, Jim Blake (shaking hands with Cal Poly President Julian McPhee), Hugh Kroupa, Gordon Moore, President McPhee, Jim Cochran, Rodney Clare. Kneeling: Vic Tomei, Bill Gallagher.